Religious concerns of dowry and marriage gifts regarding determination of their limits: study of Malaysian law - Kamal, Ahmad Haziq Haikal; Sitiris, Miszairi; Razali, Mohamad Afiq (School of Religious and Social Studies, Faisalabad (38000), Pakistan, 2021)
In 2010, the Islamic religious department of a state in Malaysia issued a fatwa, which ruled that the dowry rate in the state would be regulated at a minimum value of RM 300, with no indication of a maximum amount. In this instance, the community appears to be more concerned with the function of the provision of gift money, which is used solely to fund wedding expenses, rather than with the potential of dowry, which plays a more significant role for women. While this research does not challenge the fatwa’s decision, it does attempt to elucidate the issue of determining the minimum dowry rates from the perspective of fiqh and the Islamic Religious Administration Enactment. The library technique and inductive reasoning are by far the most often used ways of data collection by the author. On the whole, dowry has no specific limit while there are opinions of scholars on this, the setting of this dowry restriction, in particular, was never specified by Islām. People in the community misinterpret the meaning of the minimum and maximum limits, which leads to the low dowry and the high importance given to the provision of gift money.